Comparison of CT volumetric measurement with RECIST response in patients with lung cancer - Hayes, S.A.; Pietanza, M.C.; O’Driscoll, D.; Zheng, J.; Moskowitz, C.S.; Kris, M.G.; Ginsberg, M.S. (European journal of radiology, 2016)
To examine the correlations between uni-dimensional RECIST and volumetric measurements in patients with lung adenocarcinoma and to assess their association with overall survival (OS) and progression-free survival (PFS). In this study of patients receiving chemotherapy for lung cancer in the setting of a clinical trial, response was prospectively evaluated using RECIST 1.0. Retrospectively, volumetric measurements were recorded and response was assessed by two different volumetric methods at each followup CT scan using a semi-automated segmentation algorithm. We subsequently evaluated the correlation between the uni-dimensional RECIST measurements and the volumetric measurements and performed landmark analyses for OS and PFS at the completion of the first and second follow-ups. Kaplan–Meier curves together with log-rank tests were used to evaluate the association between the different response criteria and patient outcome. Forty-two patients had CT scans at baseline, after the first follow up scan and second followup scan, and then every 8 weeks. The uni-dimensional RECIST measurements and volumetric measurements were strongly correlated, with a Spearman correlation coefficient (ρ) of 0.853 at baseline, ρ=0.861 at the first followup, ρ=0.843 at the 2nd followup, and ρ=0.887 overall between-subject. On first follow-up CT, partial responders and non responders as assessed by an “ellipsoid” volumetric criteria showed a significant difference in OS (p=0.008, 1-year OS of 70% for partial responders and 46% for non responders). There was no difference between the groups when assessed by RECIST criteria on first follow-up CT (p=0.841, 1-year OS rate of 64% for partial responders and 64% for non responders). Volumetric response on first follow-up CT may better predict OS than RECIST response. Assessment of tumor size and response is of utmost importance in clinical trials. Volumetric measurements may help to better predict OS than uni-dimensional RECIST criteria.